MECHANICAL ENGINEERING APPLIED TO MINING: INNOVATIONS IN EQUIPMENT AND PROCESSES - Viana, Josimar Santos (LUMEN ET VIRTUS, 2024)
Mechanical engineering drives important advances in mining through innovative equipment design and optimized processes. The application of autonomous vehicles and digital systems has improved efficiency and safety in operations, allowing machines such as haul trucks and crushers to increase productivity and minimize human exposure to risk in environments that demand heavy ore transport and fragmenting. Predictive maintenance, using sensor-based monitoring and data analysis, assists engineers in anticipating failures, reducing downtime, and supporting informed decision making—crucial for strategic operation of complex machines like centrifugal pumps and vibrating screens. Material innovations, such as wear-resistant alloys used in grinding or classifying equipment, contribute to longer operational lifespans and reduce costs associated with part replacement. The use of remote operation centers and advanced control in processes such as comminution (crushing and grinding) and flotation helps engineers optimize energy use, material recovery, and reduce environmental impact. Additive manufacturing is emerging as a solution for faster local production of spare parts, decreasing the reliance on supply chains and ensuring faster equipment recovery. These innovations reflect the central role of mechanical engineering in shaping an efficient, sustainable, and safe future for mining operations—in an industry where maintenance and reliability strategies, continuous improvement, and multidisciplinary collaboration yield increasing operational benefits for mineral extraction and processing.